1985
DOI: 10.1677/joe.0.1040069
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of gonadectomy on sensitivity to testosterone of brain centres associated with gonadotrophin negative feedback and with mating behaviour in rams

Abstract: Castrated sheep were used to study the effects of gonadectomy on sensitivity to testosterone of brain centres associated with gonadotrophin negative feedback and with mating behaviour. In the first experiment serum LH and FSH concentrations were determined in intact rams, recently castrated (2 days and 3 weeks) and long-term castrated animals (greater than 2 years, wethers) during intravenous testosterone infusion at physiological and supraphysiological levels. In intact rams, testosterone infusions effectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Pharmacological administration of T, dihydrotestosterone (DHT) in combination with E 2 , or E 2 alone have been effective in stimulating or restoring male sexual behaviors in species such as cattle (Dykeman et al, 1982) and sheep (Clegg et al, 1969;Parrott, 1978, D'Occhio andBrooks, 1980), depending on the stage in life during which the animals were castrated (i.e., castration before or after puberty). Treatment of 2-yr-old castrated rams with implants of T and E 2 for 6 wk was sufficient to stimulate mounting of estrous ewes by these males (D'Occhio et al, 1985). D'Occhio and Brooks (1980) found that mounting behavior could be stimulated in rams castrated prepuber-tally when they were implanted s.c. with pharmacological concentrations of E 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological administration of T, dihydrotestosterone (DHT) in combination with E 2 , or E 2 alone have been effective in stimulating or restoring male sexual behaviors in species such as cattle (Dykeman et al, 1982) and sheep (Clegg et al, 1969;Parrott, 1978, D'Occhio andBrooks, 1980), depending on the stage in life during which the animals were castrated (i.e., castration before or after puberty). Treatment of 2-yr-old castrated rams with implants of T and E 2 for 6 wk was sufficient to stimulate mounting of estrous ewes by these males (D'Occhio et al, 1985). D'Occhio and Brooks (1980) found that mounting behavior could be stimulated in rams castrated prepuber-tally when they were implanted s.c. with pharmacological concentrations of E 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Sexual behavior declines in sexually experienced adults after castration and may take up to 12 months before rams completely lose interest D'Occhio and Brooks, 1980). On the other hand, treatment with testosterone stimulates sexual behavior in rams castrated either before puberty Mattner et al, 1976;D'Occhio and Brooks, 1980;D'Occhio and Brooks, 1982;Parrott and Baldwin, 1984;D'Occhio et al, 1985) or after puberty Mattner, 1976). Likewise, the restoration of sexual behavior with hormone replacement therapy is not immediate but occurs after a few weeks of treatment.…”
Section: Hormonal Control Of Sexual Behavior In Adult Ramsmentioning
confidence: 99%
“…Aromatase is enriched within brain regions important for the control of male reproductive behaviors Roselli et al, 2000). Treatment of castrated rams with estradiol stimulates sexual behaviors (Mattner, 1976;Parrott, 1978;D'Occhio and Brooks, 1980;D'Occhio and Brooks, 1982;Parrott and Baldwin, 1984;D'Occhio et al, 1985), but the treatment with the nonaromatizable dihydrotestosterone is ineffective (Parrott, 1978;D'Occhio and Brooks, 1982;Parrott and Baldwin, 1984;D'Occhio et al, 1985). In rodents estrogens and androgens synergize to stimulate copulatory behavior (Sachs and Meisel, 1994), however, such synergism has not been consistently reported for rams (Mattner, 1976;Parrott, 1978;D'Occhio and Brooks, 1980;Parrott and Baldwin, 1984).…”
Section: Hormonal Control Of Sexual Behavior In Adult Ramsmentioning
confidence: 99%
“…The rapid rise in plasma concentrations of the gonadotropins LH and FSH after castration of rams [1][2][3][4][5][6][7] indicates that secretion of the gonadotropins is under the negative feedback control of testicular hormones. While control of FSH and LH secretion by the negative feedback of testicular steroids has been studied extensively in rams, the importance of the testicular glycoprotein hormone inhibin as a feedback regulator is less well understood.…”
Section: Introductionmentioning
confidence: 99%
“…While control of FSH and LH secretion by the negative feedback of testicular steroids has been studied extensively in rams, the importance of the testicular glycoprotein hormone inhibin as a feedback regulator is less well understood. Many studies have shown that both androgens and estrogens negatively regulate the secretion of FSH and LH [1][2][3][4][5][6][8][9][10][11][12][13][14][15], although the doses of testicular steroids used have not always been in the physiological range. When a physiological dose of testosterone was administered to castrated rams for 7 days, the plasma concentrations of LH were reduced into the range of values found in intact rams but there was no significant reduction of plasma concentrations of FSH [16].…”
Section: Introductionmentioning
confidence: 99%